Let's solve the equation step by step and fill in the missing terms and descriptions.
Starting with the equation: \[ 7u - 18 - 12u = 2 \]
-
Combine like terms: \[ 7u - 12u - 18 = 2 \] \[ -5u - 18 = 2 \]
-
Add 18 to both sides: \[ -5u = 2 + 18 \] \[ -5u = 20 \]
-
Divide both sides by -5: \[ u = \frac{20}{-5} \] \[ u = -4 \]
Now we can summarize the missing descriptions and complete the process:
Missing terms:
- Combine like terms: (–5u = 20)
- Add 18 to both sides: (–5u = 20)
- Divide both sides by: (–5)
The completed process is:
-
Combine like terms.
- From \( 7u - 12u - 18 = 2 \) to \( -5u - 18 = 2 \).
-
Add 18 to both sides.
- From \( -5u - 18 = 2 \) to \( -5u = 20 \).
-
Divide both sides by -5.
- From \( -5u = 20 \) to \( u = -4 \).
Thus, the final answer for \( u \) is \( -4 \).